The 149 / 5.000 SEMINAR PROCEEDINGS XI National Seminar on Service-Learning CREA + Comprehensive Training and Meaningful Engagement November 21 and 22, 2025: Actas de Seminario (Revista Electrónica Diálogos Educativos. REDE, 2025)
Seminar minutes book. Editorial board. NETWORK.